2006
DOI: 10.1016/j.jvs.2006.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of acute critical ischemia secondary to blunt tibial artery injury

Abstract: We report a case of acute limb-threatening ischemia from blunt traumatic tibial arterial disruption managed with endoluminal techniques. An otherwise healthy 37-year-old man involved in a motorcycle crash sustained a compound fracture of his right tibia and fibula. Arterial insufficiency developed after surgical reduction of the orthopedic injuries that warranted selective angiography of the involved extremity. This demonstrated complete occlusion of the infrageniculate circulation at the level of the ankle. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Although balloon-expandable stents and covered stents have been used successfully, self-expanding stents are preferred to minimize flexibility limitations in mobile arteries. [6][7][8] Self-expanding stents are oversized by 10 to 20% of the diameter of the injured vessel to optimize apposition. Lastly, informing the trauma team of your facility's endovascular capabilities through presentations or participation in morning report is vital to ensuring that trauma patients have access to endovascular management of their injuries.…”
Section: General Principlesmentioning
confidence: 99%
“…Although balloon-expandable stents and covered stents have been used successfully, self-expanding stents are preferred to minimize flexibility limitations in mobile arteries. [6][7][8] Self-expanding stents are oversized by 10 to 20% of the diameter of the injured vessel to optimize apposition. Lastly, informing the trauma team of your facility's endovascular capabilities through presentations or participation in morning report is vital to ensuring that trauma patients have access to endovascular management of their injuries.…”
Section: General Principlesmentioning
confidence: 99%
“…However, in trauma cases, open reconstruction is difficult because of lower-extremity edema and vasospasm of the injured vessels (6). Patient 1 had compound open fractures with contaminated wounds, so surgical bypass was considered to have a high infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, balloon angioplasty in combination with surgery, transcatheter embolization of hemorrhagic lesions, and stent or stent graft placement for dissecting or hemorrhagic lesions have been introduced (2,7). However, reports of treatment of occlusive lesions are limited (6). …”
Section: Discussionmentioning
confidence: 99%
“…Alvarez-Tostado, et al reported a successful treated case of acute critical ischemia secondary to blunt tibial artery injury by endovascular maneuver. 4) Recanalization of the injured posterior tibial artery was achieved by using coronary balloon-expandable stents. In this case, we did not consider endovascular treatment because surgical exposure and revision of the saphenous vein graft was considered to be easy.…”
Section: Discussionmentioning
confidence: 99%